Counterstrike - Black, Peter Jay (New York : Bloomsbury, 2016)
c
"First published in Great Britain in April 2016.
HL620L
Decoding demand: 94 (very high) Semantic demand: 100 (very high) Syntactic demand: 88 (very high) Structure demand: 87 (very high)
Accelerated Reader AR
Keywords: Orphans -- Fiction; Computer viruses -- Fiction; Criminals -- Fiction; Science fiction